Longevity and Lifetime Education : Global Evidence from 919 Surveys - Hoque, Mohammad Mainul (World Bank, Washington, DC, 2017)
Data from 919 household surveys conducted between 1960 and 2012, spanning 147 economies, are used to evaluate the relationship between rising life expectancy at birth and lifetime years of schooling for successive birth cohorts between 1905 and 1988. The study finds significant positive effects of increased life expectancy at birth on lifetime completed years of schooling in 95 percent of the surveys, with significant negative effects found in only 2.3 percent. Rising life expectancy at birth for a birth cohort has intergenerational benefits in that the cohort's children’s schooling also increases. Rising life expectancy at birth since 1905 can explain 70 percent of the rising completed years of schooling for those birth cohorts.